PERTANGGUNGJAWABAN HUKUM DALAM PEMBELAAN NOTARIS TERHADAP INVESTIGASI YANG DILAKUKAN OLEH MAJELIS PEMERIKSA PUSAT NOTARIS. (STUDI KASUS PUTUSAN MAJELIS PEMERIKSA PUSAT NOTARIS PUTUSAN MPPN NOMOR 03/B/MPPN/2017 DAN PUTUSAN PENGADILAN TATA USAHA NEGARA JKT - Regina Ayu Sepriani; Sonyendah Retnaningsih (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
A notary is a public official who is authorized to make an authentic deed where the reason for the position of a notary arises is because of the needs of the community which is then created and socialized to the public. In addition, a notary has a function in making a deed of establishment, transfer of shares and also a deed of amendment to the articles of association of a Limited Liability Company, which if a notary is not careful in making and entering legal events, the notary can be subject to sanctions and reported to the Notary Central Supervisory Council.